Exploring old buildings of Sungai Petani as young generation's preferred city - Ismail, Alwani (2018)
Heritage trail concept is the good ways to lead people especially at Old Town City of Sungai Petani. The formation of heritage trail normally has given prior attention to people to explore every spaces. Despite the potential of heritage trail for other fields or purpose are rarely explored. This study is significance to the domain of urban design framework, young generation intention, preserving of old buildings, explore, experience and gain knowledge related to the initial planning and design of heritage trail. The methodology of the study involves the implementation stages of primary data from observing and interview meanwhile secondary data from government department and existing data from previous researcher that ready published. Based on the design idea and concept of ‘ribbon of GENERATION’ that has been transform into physical form into designing a spaces to be functioning for people especially young generation to explore and experience the Old Town of Sungai Petani, the preserving of the heritage buildings and heritage route system to make spaces more alive with a modern touches that blended together at Old Town City of Sungai Petani.